DIALEKTIKA PARADIGMATIK BUDAYA POLITIK LOKAL DAN DEMOKRASI DAN PENGARUHNYA TERHADAP STRUKTUR ANATOMI TEORITIK DEMOKRASI DI DAERAH (Studi Kasus Demokrasi Lokal Di Jawa Timur) - LABIB , AHMAD (2011)
Modern conceptions of democracy is the result of a long way of dialectical process between the original text and the local cultural context of Modern European society. Secularism, the idea of sovereignty, freedom, and constitutionalism emerged dialectically construct theoretical convergence which then form the face of modern democracy. Although he has composed a relatively well-established conception of democracy, but democracy remains a concept that is open to the elements of a typical local political culture. Openness that allows democracy has many variants with theoretical anatomical structure different in every political community. This study was designed to prove the possibility. Using a qualitative approach through case studies of local democracy in East Java, the study examines the dialectical relationship between the paradigmatic elements of local political culture in East Java with democracy, and its influence on the theoretical anatomical structure of local democracy. This research revealed that in East Java, the conception of deliberative democracy tend to be patterned, in contrast to Western-model liberal democracy. It's caused by the paradigmatic elements of the local political culture in East Java are different from paradigmatic elements of the political culture of Europe. In East Java, there are four basic paradigmatic elements supporting the local political culture, which are: belief in relegiusm an inclusive, egalitarian principles of God' s sovereignty, communitarianism, and the humanizing power of the state. Four elements were then formed the theoretical anatomical structure that consists of local democracy: The state religion in a pluralistic conception, transcendental popular sovereignty, political and economic deliberation, and deliberative constitutionalism. Configuring the theoretical anatomy of local democracy in East Java that created a different variant of local democracy with the concept of origin.